2000
DOI: 10.1037/0022-006x.68.4.641
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid psychopathology in binge eating disorder: Relation to eating disorder severity at baseline and following treatment.

Abstract: Individuals with binge eating disorder (BED) have high rates of comorbid psychopathology, yet little is known about the relation of comorbidity to eating disorder features or response to treatment. These issues were examined among 162 BED patients participating in a psychotherapy trial. Axis I psychopathology was not significantly related to baseline eating disorder severity, as measured by the Structured Clinical Interview for DSM-III-R (SCID-I and SCID-II) and the Eating Disorder Examination. However, presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
128
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 34 publications
18
128
3
4
Order By: Relevance
“…In common with other studies, 10,17 we found that BED and NBE subjects did not differ on either the EDE Restraint or TFEQ Cognitive Restraint subscales. Perhaps BED in extreme obesity is more a result of greater disinhibition, while the extreme obesity in both groups may be related to relatively low 'restraint'.…”
Section: Discussionsupporting
confidence: 71%
“…In common with other studies, 10,17 we found that BED and NBE subjects did not differ on either the EDE Restraint or TFEQ Cognitive Restraint subscales. Perhaps BED in extreme obesity is more a result of greater disinhibition, while the extreme obesity in both groups may be related to relatively low 'restraint'.…”
Section: Discussionsupporting
confidence: 71%
“…A recent study using the SCID-II with BED individuals found that Cluster B personality disorders predicted higher levels of binge eating at 1 year posttreatment (Wilfley et al, 2000). A study by Eldredge, Locke, and Horowitz (1998) found that among a sample of individuals with BED, poor treatment outcome was associated with distress over problems with social avoidance.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Axis II psychopathology was determined on a continuum of symptomatology (summation of threshold and subthreshold symptoms) for the current study, based on the finding that the use of a continuous symptom measure is most likely to be associated with the severity of eating disorders (Wilfley et al, 2000).…”
Section: Scid-iimentioning
confidence: 99%
See 2 more Smart Citations